Forms of inheritance of musical instruments in the culture of the peoples of the North Caucasus and Kazakhstan - A. N. Sokolova; Z. N. Smakova (Вестник Майкопского государственного технологического университета, 2024)
The relevance of the research is determined by the need to identify the common and special in the cultures of peoples living on different continents and not having common borders. The goal is to identify ethnographic communities in matters of sacralization and forms of inheritance of musical instruments in the culture of the peoples of the North Caucasus and Kazakhstan. The work uses a systematic typological method and a method of ethnographic description of material and spiritual values, partly preserved to this day and partly transformed due to changed sociocultural realities. Based on modern ﬁeld research in the villages of Adygea and Kazakhstan, archival sources and scientiﬁc literature, the authors were able to establish that the transfer of musical instruments from the older generation to the younger was carried out under certain conditions. One of the most important conditions was the requirement to keep the tool in working condition, i.e. do not let the instrument be silent. Another important condition is to transfer the instrument into the hands of a chosen one (a worthy musician), who takes upon himself «amanat» – undertakes to cherish the music (preserve musical traditions). The speciﬁc fulﬁllment of ethnographic conditions for observing the tradition of inheritance of musical instruments shows their similarities and differences in the synchrony of the past and diachrony the last one and a half centuries. Changes in the nomenclature of musical instruments in modern times have also led to changes in their forms of inheritance. Instruments began to be preserved by relatives as a memory of a famous ancestor or transferred to a museum for the same purpose. It is not the musical instruments that become more valuable, but the musical or sound documents that record the cultural heritage of the past.The novelty of the research is associated with the presentation of previously unpublished ethnographic facts collected in the ﬁeld and their original interpretation.